RENINOMA: A SURGICALLY CURABLE CAUSE OF HYPERTENSION - Krishnan, Gaayathri (Journal of the ASEAN Federation of Endocrine Societies, 2023)
INTRODUCTION/BACKGROUND Reninoma is an extremely rare cause of hypertension. It is a tumour of the juxtaglomerular apparatus which secretes renin, leading to secondary hyperaldosteronism, ultimately causing hypertension. This disease is commonly seen in adolescents and young adults and has a female preponderance. Patients with reninoma mostly present with hypokalaemia although they can also be normokalaemic. Most reninomas are benign and surgical resection can render the patient normotensive. Here we report a case of reninoma in a young female who presented with hypertension and palpitations. CASE We describe a 23-year-old female who was referred for evaluation of hypertension in the young. She was found to have a BP ranging between 130-180 mmHg (systolic) and 85-120 mmHg (diastolic). She was diagnosed with hypertension and started on oral doxazocin. She complained of paroxysms of sweating with palpitations. On examination, she was a moderately built female with a body mass index of 20.4kg/m2. Her pulse rate was 100 beats per minute and her BP was 153/100 mmHg. Her renin levels were elevated at 518 mU/L (NV: 4.4- 46.1 mU/L) with elevated aldosterone at 998 pmol/L (NV: 61.2- 997.8 pmol/L). Computed tomography of abdomen and pelvis revealed the presence of a well encapsulated heterogeneously enhancing mass on the upper pole of the right kidney measuring 2.7 x 3.0 x 3.3 cm. A biopsy of the lesion was suggestive of a reninoma. The patient underwent a nephron-sparing surgery. Histopathological examination revealed an encapsulated lesion that stained positive for CD 34, CD 177 and vimentin, confirming the diagnosis. Following surgery, the patient was normotensive and all anti-hypertensive medications were withheld. CONCLUSION Reninomas are mostly benign neoplasms that can lead to hypertension and severe end-organ damage. High clinical suspicion is required to diagnose this disease, and nephronsparing surgery can render the patient normotensive.